The demand for money : theories and evidence - Laidler, David E. W. (New York : Dun-Donnelley, 1977)
The book examines the current state of knowledge about the demand side of money market. It also seeks to give an up-to-date account about the branch of macroeconomics.
Includes index.
Bibliography: p. 171-177.
usc 19/09/18
Loans
Keywords: Demand for money; Money; Demand for money--Mathematical models; Money--Mathematical models